1997
DOI: 10.1021/jp971399p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Alcohol Solutions on the Thermal Transition of Lysozyme:  A Calorimetric Study

Abstract: Thermal denaturation of lysozyme has been studied at pH = 3 in water/ethanol and water/tert-butyl alcohol mixtures in the water rich region of composition (mole fraction of cosolvent x 2 < 0.12) by high-sensitivity differential scanning calorimetry. The results show that on increasing alcohol concentration, the enthalpy and entropy of denaturation of lysozyme first reach a maximum at an intermediate composition x 2 = typical for each alcohol ( ≅ 0.06 for ethanol and ≅ 0.02 for tert-butyl alcohol) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 18 publications
4
56
0
Order By: Relevance
“…The thermal denaturation of lysozyme has been studied in TBA-water and ethanol-water mix-tures, finding that there is a relationship between the microstructure of the solvent and the conformation of the protein. 8 However, the authors suggested that the alcohols affected the conformation of protein via an indirect mechanism with structural reorganization of water and there was no direct interaction between the alcohols and the protein, 8 which was different from the conclusion from other reports. [3][4][5][6] The previous work from our group described thermodynamic properties of amino acids, the model compounds of protein, in several alcohol-water mixtures.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…The thermal denaturation of lysozyme has been studied in TBA-water and ethanol-water mix-tures, finding that there is a relationship between the microstructure of the solvent and the conformation of the protein. 8 However, the authors suggested that the alcohols affected the conformation of protein via an indirect mechanism with structural reorganization of water and there was no direct interaction between the alcohols and the protein, 8 which was different from the conclusion from other reports. [3][4][5][6] The previous work from our group described thermodynamic properties of amino acids, the model compounds of protein, in several alcohol-water mixtures.…”
Section: Introductionmentioning
confidence: 85%
“…In the range 0 mol•L -1 ≤c TBA ≤2.5 mol•L -1 , the hydrodynamic radius of BSA exhibits an S type behavior, which is almost the same as the TBA concentration dependence of hydrodynamic radius of lysozyme. 26 On the basis of the thermal denaturation of lysozyme in TBA-water and ethanol-water mixtures, Onori 8 suggested that the net consequence of the effect of hydrophobic hydration was to enhance the solubility of nonpolar species and to disfavor their aggregation and that hydrophobic interactions at a concentration of hydrophobic groups lower than a critical concentration were repulsive and gave a destabilizing contribution to the native structure of protein. Thus, the attenuation of these interactions due to alcohol addition should favor clustering of hydrophobic groups and lead to a more compact conformation of protein.…”
Section: Conformational Change Of Bsa In Tba-water Mixturesmentioning
confidence: 99%
See 3 more Smart Citations